Reclaiming local control through superintendents, school boards, and community activism - Mountford, Meredith; Wallace, Leigh (Research on the superintendency, 2022)
"In 1987, Jacqueline Danzberger described school boards as the forgotten players. However, things have changed drastically for school boards over the past few years. No longer are school boards the forgotten players in school governance. Instead, school boards often find themselves in the center of controversies stemming from the intrusion of political partisanship into local governance structures which historically, and for the purposes of sustained democratic educational governance, were intentionally intended to be non-partisan elected boards. However, this is where many school boards find themselves today. The chapters in this volume address several key questions school board members are currently facing as they struggle to protect some of our country's earliest guardrails of democracy; local control of schools. To be sure, school boards are no longer the forgotten players. Implications of this may be wide reaching and therefore deserve room in the current literature on educational governance. Volume II of the Research on the Superintendency series highlights recent research on school boards, local control, governance, and the superintendency. Each chapter is briefly described in this chapter and the chapters are in a particular order that readers may wish to pay attention to as they enjoy the book. The first three chapters deal with local control in both rural and urban settings. The next two chapters are studies focused mainly on school boards and how their roles have shifted over the years followed by a chapter on the relationship between school boards and their superintendents within a regulatory environment and the level of stress it can bring to board members and superintendents. The final five chapters describe recent superintendent research that is closely linked to school governance or school board policies. We ask readers to juxtapose lessons learned in those five chapters to the role of school boards within the context of those chapters"--